The Implementation of Islamic Educational Values in Life Skills Education for Female Students at TMI Putri Al-Amien Prenduan Sumenep Madura - Muru’Atul Afifah; ‘Afifah Vitaqorrubillah (Values: Jurnal Kajian Islam Multidisiplin, 2025)
Education must create a learning atmosphere that provides life skills for students. At TMI Putri Al-Amien Prenduan, apart from the religious aspect, female students are also taught life skills education. This research focuses on forms of life skills education at TMI Putri Al-Amien Prenduan and the implementation of Islamic educational values in life skills education. In this research, researchers used a descriptive qualitative research approach. The methods used in this research are observation, interviews and documentation. Data sources were obtained from several female students, supervisors, teachers, and senior teachers. Forms of life skills education include personal skills, social skills, academic skills and vocational skills. Implementation of Islamic education values includes the values of aqidah, khuluqiyyah, and worship.